A Review of Microinvasive Combined Phaco-Vitrectomy: Recent Technical Advances - Mercanti, Andrea (Ophthalmol Ther, 2017)
Combined cataract and vitreoretinal surgery results in better compliance in patients with posterior segment pathology and should be the preferred approach to reduce the high rate of cataract development after vitreoretinal surgery and to improve earlier visual acuity. Technological advances in both anterior and posterior segment surgery are leading to the development of instruments with a smaller diameter and more efficient tools, resulting in a minimizing of the tissue trauma related to the surgery, acceleration of functional recovery and increasing patient comfort. In this review we report on recent advances that allow this miniaturization process while maintaining the efficacy and safety of microinvasive combined surgical procedures, with a focus on pumps, illumination, phaco tip and the vitrectomy probe.